(3WHbGJ GdTGaYjIs - (3YHO GdQMje Hf GdMSf Hf Ydj GdESfhj GdTGaYj, CHh eMeO, LeGd GdOjf,J (B772 (3g` s ((3eMeO Hf GdMGL jYbhH Hf eMeO Hf Ydi GdJGLQ aj GdZdGd s)
(3ChdgG (B:s
(3GdMeO ddg eejJ GdCMjGA heMji GdCehGJ, hoeYjO GdNdGFb ef GddMhe GdoeJeRbI hGdYXGe GdQaGJ s
(3BNQgG (B:s
(3hai gPG GdbOQ caGjI Je GdcJGH eNJJekG HgPG GdbGfJ GdGhGH, hGddg Gdoehab ddUhGH, hEdjg GdeQLY hGdeBH, hdg GdMeO XGgQkG hHGWfkG, hfYe Gdhcjd s
(3GfXQ Qbe (B311 (3JGQjNs
(3fSNI QGHYIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B344 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B203s
Keywords: (3GdJGQjNs